Comparative studies on English translation of the four main characters’ titles in “Xiyouji” - Deng, Lulu; Abdullah, Muhammad Alif Redzuan; Wong, Ling Yann (Sciedu Press, 2024)
The study aims to compare Anthony C. Yu‘s and W. J. F. Jenner‘s translations of the four main characters‘titles in ―Xiyouji.” By categorizing the main characters‘titles using a statistical methodology and determining what the characters‘personalities are embodied in the main titles, the study analyzes which translation is more appropriate from the perspective of cultural communication. The most frequently used titles for ―孙悟空(Sun Wukong)” are ―(孙)行者(Pilgrim/Moneky)” and ―(齐天)大圣(Great Sage),” accounting for 48% and 14% of his 119 titles. For ―唐玄奘(Tang Xuanzang),” the predominant titles are ―师父(Mater)” and ―三藏(Sanzang/Tripitaka),” making up 40% and 25% of his 17 titles. ―猪悟能(Zhu Wuneng)” is most commonly called ―(猪)八戒(Eight Rules/Pig)” and ―呆子(Idiot),” constituting 73% and 18 % of his 11 titles. As for ―沙悟净(Sha Wujing),” the prevalent titles are ―沙和尚(Sha Monk)” and ―悟净(Wujing),” encompassing 90% and 7% of his seven titles. Whether Sun Wukong‘s justice, braveness and supernatural ability and his role as the crisis solver of the pilgrimage, Tang Sanzang‘s wisdom, leadership and enlightenment and role as the leader, Zhu Wuneng‘s transgressive nature and role as the rule breaker or Sha Wujing‘s devoutness and role as the follower, their titles reflect their personalities and positions in the narrative. By comparing Yu‘s and Jenner‘s translations of these titles, the paper observes that Yu‘s translation conveys the implied meanings. In contrast, Jenner‘s translation is straightforward and simplified. Yu‘s translation is more beneficial for the target language readers to understand Chinese Culture.